2014
DOI: 10.1158/0008-5472.can-14-0683
|View full text |Cite
|
Sign up to set email alerts
|

FL118 Induces p53-Dependent Senescence in Colorectal Cancer Cells by Promoting Degradation of MdmX

Abstract: Anticancer agent FL118 was recently identified in screening of small-molecule inhibitors of human survivin expression. Although FL118 is a camptothecin analogue, its antitumor potency is much superior to other FDA-approved camptothecin analogues (irinotecan and topotecan). The mechanism of action (MOA) underlying the antitumor effects of FL118 remains to be fully elucidated. Here, we report that FL118 activates tumor suppressor p53 as a novel MOA in p53 wild-type cancer cells. Our studies show that this MOA in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 46 publications
2
42
0
Order By: Relevance
“…Recently, many novel small molecules with promising activity have been published as MDM2 inhibitors, including a new synthetic approach to obtain stapled peptides, chlorofusin‐inspired class of analogues, fluorescent triazolylpurines, sulfamide and triazole benzodiazepines, oxazoloisoindolinones, dispiroindolinones, a camptothecin analogue (FL118), and an inauhzin analogue, among others. Also, a 2,3′‐bis(1 H ‐indole) scaffold was recently published showing additional hydrophobic interactions with the p53 Val93 as indicated by 2D NMR and modeling studies .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many novel small molecules with promising activity have been published as MDM2 inhibitors, including a new synthetic approach to obtain stapled peptides, chlorofusin‐inspired class of analogues, fluorescent triazolylpurines, sulfamide and triazole benzodiazepines, oxazoloisoindolinones, dispiroindolinones, a camptothecin analogue (FL118), and an inauhzin analogue, among others. Also, a 2,3′‐bis(1 H ‐indole) scaffold was recently published showing additional hydrophobic interactions with the p53 Val93 as indicated by 2D NMR and modeling studies .…”
Section: Discussionmentioning
confidence: 99%
“…Shepherdin is the first example of this type of survivin inhibitors and was rationally designed in 2005 [4]. Shepherdin, a survivin 79 KHSSGCAFL 87 (minimum: 79 KHSSG 83 ) peptidomimetic agent, interrupts heat shock protein (Hsp) 90 interactions with survivin [4,5]. Alternatively, shepherdin was incorporated into cancer cells using adenovirus-mediated expression systems, thus demonstrating a proof of principle for use of agents that disrupt survivin-Hsp90 binding as an anticancer agent [6,7].…”
Section: Inhibitors That Disrupt Survivin Interactions With Its Partnmentioning
confidence: 99%
“…DNA microarray studies showed that FL118 does not inhibit the expression of cIAP1, Bcl-2, Bcl-XL, Bcl-2, Bcl2A1, Bcl-w, Bcl-B, Bcl2L12, Bcl2L13, Bcl-G and Bcl2L15 (unpublished data), indicating additional selectivity of FL118 in its molecular targets. Furthermore, FL118 also inhibits MdmX/Mdm4 [79], a critical oncogenic protein involved in p53 pathway, and ERCC6 [80], a critical regulator in DNA repair. Importantly, while FL118 downregulation of MdmX induced senescence in cancer cells with wild type p53, FL118 exhibits even higher efficacy to inhibit cell growth and induce apoptosis in cancer cells without functional p53 (mutated or null) [79].…”
Section: Fl118mentioning
confidence: 99%
“…MDMX binds to p53 and is involved in inhibiting p53 transactivation activity, which represses function of p53 and destabilizes the protein in breast cancer cells (14,36). Our data indicated that metformin reduced MDMX level and activated p53 to regulate apoptosis-related proteins.…”
Section: Discussionmentioning
confidence: 70%